Bimbingan Kelompok Sebagai upaya Membangun Keberanian Berpendapat pada Diri Santri Putra Kelas VIII MTsS Al-Falah Kota Padang - Putra, Ahmad (Institut Agama Islam Negeri Padangsidimpuan, 2021)
This research aims to find out the steps and efforts made by counseling guidance teachers in carrying out group guidance activities with the aim of building courage to argue in the children of class VIII MTsS Al-Falah Kota Padang. This research is a field study using a qualitative approach. The subjects in this field study were 2 (two) counseling guidance teachers and 8 (eight) students of class VIII MTsS Al-Falah Kota Padang. Data collection through observation, interviews and documentation. As for data analysis using qualitative descriptive, the data that has been obtained is then compiled and classified so that it can answer from the problem formulation above. The results obtained from the utilization of group guidance services accompanied by the use of punishment that educates is that class VIII MTsS Al-Falah began to build the courage to issue opinions in group guidance activities. As a result, students are not afraid to be wrong in issuing their arguments and begin to venture to argue according to the topic discussed.